A comprehensive update of siRNA delivery design strategies for targeted and effective gene silencing in gene therapy and other applications. (1st February 2023) - Abosalha, Ahmed Khaled; Ahmad, Waqar; Boyajian, Jacqueline; Islam, Paromita; Ghebretatios, Merry; Schaly, Sabrina; Thareja, Rahul; Arora, Karan; Prakash, Satya
ABSTRACT: Introduction: RNA interference (RNAi) using small interfering RNA (siRNA) is a promising strategy to control many genetic disorders by targeting the mRNA of underlying genes and degrade it. However, the delivery of siRNA to targeted organs is highly restricted by several intracellular and extracellular barriers. Areas covered: This review discusses various design strategies developed to overcome siRNA delivery obstacles. The applied techniques involve chemical modification, bioconjugation to specific ligands, and carrier-mediated strategies. Nanotechnology-based systems like liposomes, niosomes, solid lipid nanoparticles (SLNs), dendrimers, and polymeric nanoparticles (PNs) are also discussed. Expert opinion: Although the mechanism of siRNA as a gene silencer is well-established, only a few products are available as therapeutics. There is a great need to develop and establish siRNA delivery systems that protects siRNAs and delivers them efficiently to the desired sitesare efficient and capable of targeted delivery. Several diseases are reported to be controlled by siRNA at their early stages. However, their targeted delivery is a daunting challenge.